INTERNALISASI NILAI MORAL DALAM KELUARGA SEBAGAI BASIS PEMBENTUKAN KARAKTER ANAK - Muhammad Fauzan Supardin; Muh. Sudirman; Imam Suyitno (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2026)
Abstract: The formation of children's morals within the family environment is a crucial process involving the inculcation of noble values, ethics, and good behavior from an early age. The family serves as the primary foundation in developing a child's character and personality, establishing a moral basis that will guide them in social life. This study aims to analyze and describe how children's morals are formed within the family environment in Kareloe Village, Bontoramba District, Jeneponto Regency. This research employed a qualitative approach with a descriptive research type. The research location was Kareloe Village, Bontoramba District, Jeneponto Regency. The research subjects were families in Kareloe Village selected through purposive sampling. Data collection techniques used were observation, in-depth interviews, and documentation. The collected data were analyzed using data reduction, data presentation, and conclusion drawing.  Based on the research findings, it was discovered that the formation of children's morals in Kareloe Village is carried out through various methods, including: (1) examples from parents and other family members, (2) religious education and religious values, (3) habituation of good and polite behavior, (4) giving advice and reprimands, and (5) involving children in social and religious activities in the community. Nevertheless, challenges in children's moral formation were still found, such as the negative influence of social media and peer environment. The results of this study indicate that the family's role is highly dominant in the formation of children's morals in Kareloe Village. Cooperation among parents, the community, and educational institutions is expected to further strengthen the formation of children's morals to become individuals with good character and morality.